Review of: Magnussen H. (2017) The Moral Work of Nursing – Asking and Living with the Questions - Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2019)
A narrative description of personal moral challenges of a nurse serving diverse communities.